Rab27a promotes degradation of West Nile virus E protein in the lysosome - Kobayashi, Shintaro; Kawai, Seira; Fukuda, Yukine; Eguchi, Haruto; Maezono, Keisuke; Thammahakin, Passawat; Sawa, Hirofumi; Kariwa, Hiroaki (iScience, 2024)
Rab27a, a Rab family small GTPases, plays an important role in the trafficking and secretion of the intracellular proteins and has been reported to promote various viral multiplication. However, whether Rab27a is involved in West Nile virus (WNV) multiplication is unknown. This study examined the ability of Rab27a to suppress WNV multiplication. The inhibition of Rab27a expression increased viral multiplication and the intracellular levels of WNV structural proteins, E and prM proteins. Rab27a partially colocalized with E protein, mainly in the perinuclear region, while inhibition of Rab27a expression resulted in diffuse subcellular localization of E protein. In addition, some of the perinuclear E protein colocalized with the lysosomal marker LAMP1, and inhibition of lysosomal acidification increased intracellular levels of Rab27a and E proteins. These observations suggested that Rab27a inhibits WNV multiplication by inducing the degradation of viral protein in lysosomes. [Display omitted] •Rab27a inhibits WNV multiplication and the levels of intracellular E protein•Inhibition of Rab27a results in diffuse subcellular localization of E protein•Inhibition of lysosomal degradation increases E protein and Rab27a levels Virology; Cell biology